The social unconscious : selected papers - Hopper, Earl (International library of group analysis ;, 2003)
The social unconscious and its manifestations in group analysis are the focus of this important new book of Earl Hopper's selected papers. Drawing on sociology, psychoanalysis and group analysis, he argues that groups and their participants are constrained unconsciously by social, cultural and political facts and forces. These hypotheses are illustrated with clinical vignettes concerning anti-Semitism, racism, the politics of class and gender, and the effects of rapid social change. Transference and countertransference processes are examined both vividly and honestly. Theoretically generative.